PENGARUH TERPAAN DAN ISI PESAN TAYANGAN CHANNEL YOUTUBE KOK BISA EPISODE “INILAH HARGA MENGEJUTKAN DATA PRIBADI KITA” TERHADAP TINGKAT PENGETAHUAN SUBSCRIBER (Jurnal Ilmu Komunikasi, 2025)
The background of this research is due to the increasing number of cyber crimes, making the public are urged to be more careful in maintaining or using privacy data. A youtube channel called "how come", comes with a variety of content that may be needed by the public, one of which is content entitled "This is the Shocking Price of Our Personal Data". In the video it is explained that often we are not aware that we have given away a lot of our personal data voluntarily, through various challenges or trends that are viral on social media, even though our personal data is something valuable, until someone trades the data. private on the internet. This study aims to find out whether there is an influence between exposure and message content on the show "This is the Shocking Price of Our Personal Data" on the level of knowledge of subscribers about the importance of personal data. The theory used is Uses and Gratification. The research method used is a survey method - quantitative with a research sample of 400 respondents according to the respondents' criteria in this study. The data obtained and analyzed using SPSS 20.0. The results showed that there was an influence between exposure and the message content of the show Kok Bisa eps "This is the Shocking Price of Personal Data" on the level of subscriber knowledge about personal data on social media.